The ensured proliferative capacity of myoblast in serum-reduced conditions with Methyl-β-cyclodextrin - Katayama, Tomoka; Chigi, Yuta; Okamura, Daiji (Frontiers in Cell and Developmental Biology, 2023)
To produce muscle fibers for cultured meat on a large scale, it is important to expand myoblasts in a serum-reduced or serum-free medium to avoid cost, ethical, and environmental issues. Myoblasts such as C2C12 cells differentiate quickly into myotubes and lose their ability to proliferate when the serum-rich medium is replaced with a serum-reduced medium. This study demonstrates that Methyl-β-cyclodextrin (MβCD), a starch-derived agent that depletes cholesterol, can inhibit further differentiation of myoblasts at the MyoD-positive stage by reducing plasma membrane cholesterol on C2C12 cells and primary cultured chick muscle cells. Furthermore, MβCD efficiently blocks cholesterol-dependent apoptotic cell death of myoblasts, which is one of the mechanisms by which it inhibits the differentiation of C2C12 myoblast cells, as dead cells of myoblast are necessary for the fusion of adjacent myoblasts during the differentiation process into myotubes. Importantly, MβCD maintains the proliferative capacity of myoblasts only under differentiation conditions with a serum-reduced medium, suggesting that its mitogenic effect is due to its inhibitory effect on myoblast differentiation into myotube. In conclusion, this study provides significant insights into ensuring the proliferative capacity of myoblasts in a future serum-free condition for cultured meat production.